ChemInform Abstract: A Synthesis of (.+‐.)‐Aplydactone. Issue 52 (6th December 2016) - Meier, Robin; Trauner, Dirk
Abstract: A total synthesis of the unusual brominated sesquiterpenoid aplydactone I is presented that relies on two non‐biomimetic, highly effective photochemical key steps establishing the two cyclobutane rings.